Effect of supplemental feeding at different periods on activity and build up of honey bee colonies - AbdalIaa, Mohamed A.; Khodairy, Mohammed M.; Moustafa, Adham M. (2008)
The study was carried out in apiary at Sohag region during the period from December, 2006 to March, 2007. The influence of supplemental feeding at different periods on activity and build up of honey bee colonies was studied. The feeding periods under experiment were 13week, II-week, 9-week, 7-week, 5week and 3-week. The total consumption of supplemental feeding was recorded for all feeding periods. The greatest rate of consumed food was recorded at 13-week feeding period. Positive correlations were found between supplemental feeding and both of bee population size and brood-rearing activity.
Includes reference.
Summary in Arabic.
1
Keywords: Honeybee; Honeybee -- Feeding and feeds